1988
DOI: 10.1016/0009-2509(88)87068-4
|View full text |Cite
|
Sign up to set email alerts
|

Micromixing in a static mixer and an empty tube by a chemical method

Abstract: deduced from Xs and tr. The mixing time tm was found to be about 10 times larger in an empty tube than in the static mixer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Figure shows that smaller crystals with a narrower size distribution were obtained when static mixers were used. As reported by Meyer, characteristic mixing time in an empty pipe is 1 order of magnitude bigger than the mixing time for a pipe with static mixers . As a consequence, in the experiment without static mixers the nucleation and growth of flufenamic acid had already started before micromixing in the empty crystallizer was complete, and the crystal size distribution resulting was much wider as evidenced by the higher values of coefficient of variation.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Figure shows that smaller crystals with a narrower size distribution were obtained when static mixers were used. As reported by Meyer, characteristic mixing time in an empty pipe is 1 order of magnitude bigger than the mixing time for a pipe with static mixers . As a consequence, in the experiment without static mixers the nucleation and growth of flufenamic acid had already started before micromixing in the empty crystallizer was complete, and the crystal size distribution resulting was much wider as evidenced by the higher values of coefficient of variation.…”
Section: Resultsmentioning
confidence: 67%
“…As reported by Meyer, characteristic mixing time in an empty pipe is 1 order of magnitude bigger than the mixing time for a pipe with static mixers. 48 As a consequence, in the experiment without static mixers the nucleation and growth of flufenamic acid had already started before micromixing in the empty crystallizer was complete, and the crystal size distribution resulting was much wider as evidenced by the higher values of coefficient of variation. This observation is consistent with the results reported by Mahajan for crystallization of lovastatin in two impinging jet precipitators, 20 as well as Raphael for crystallization of sunflower proteins in a tubular reactor, where operation at poorly mixed conditions resulted in large crystals with wider CSD.…”
Section: Population Balance Modelmentioning
confidence: 99%
“…Meyer et al investigated micromixing, i.e., mixing on a molecular length scale, for laminar flow in pipes with static mixers and empty pipes. They reported that the performance of the static mixer was an order of magnitude superior to a tube with no mixing elements . The enhanced mixing of the static mixers is due to a higher rate of energy dissipation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…They reported that the performance of the static mixer was an order of magnitude superior to a tube with no mixing elements. 45 The enhanced mixing of the static mixers is due to a higher rate of energy dissipation. Moreover, other authors have reported that the CFI mixer offers a higher mixing efficiency as compared to static mixers, 33,46 and it produces a lower pressure drop.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas for co-polymerizations, the time of micromixing will strongly influence the product characteristics in terms of mean molecular mass and its distribution on one hand, and the composition distribution and the sequence of monomer units on the other hand. In order to investigate and estimate the degree of micromixing, a novel test reaction using in-line sensor was developed and tested [23][24][25]. mixing efficiencies.…”
Section: Micromixingmentioning
confidence: 99%